2004
DOI: 10.1021/jp047860c
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Chemistry of Hydrofluoroethers:  Reaction of a Series of Hydrofluoroethers with OH Radicals and Cl Atoms, Atmospheric Lifetimes, and Global Warming Potentials

Abstract: The kinetics of the OH radical and Cl atom reactions with nine fluorinated ethers have been studied by the relative rate method at 298 K and 1013 hPa using gas chromatography-mass spectroscopy (GC-MS) detection: k(OH + CH3CH2OCF3) = (1.55 +/- 0.25) x 10(-13), k(OH + CF3CH2OCH3) = (5.7 +/- 0.8) x 10(-13),k(OH + CF3CH2OCHF2) = (9.1 +/- 1.1) x 10(-15), k(OH + CF3CHFOCHF2) = (6.5 +/- 0.8) x 10(-15), k(OH + CHF2CHFOCF3) = (6.8 +/- 1.1) x 10(-15), k(OH + CF3CHFOCF3) < 1 x 10(-15), k(OH + CF3CHFCF2OCHF2) = (1.69 +/- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

31
110
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(147 citation statements)
references
References 42 publications
31
110
5
Order By: Relevance
“…The interaction between atomic chlorine or OH radical with organic molecules present in the atmosphere needs a detailed understanding as it might help in controlling the ozone depletion. The interaction of oxygen bases with atomic chlorine has been investigated in several works, for example the interaction of Cl • with H 2 O [1,2], halogenated ethers [3][4][5][6][7], methylacetate [8], halogenated aldehydes [9], fluorinated alcohols [10] and halogenated alkanes [11]. For most of these systems, such as the H 2 O. .…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between atomic chlorine or OH radical with organic molecules present in the atmosphere needs a detailed understanding as it might help in controlling the ozone depletion. The interaction of oxygen bases with atomic chlorine has been investigated in several works, for example the interaction of Cl • with H 2 O [1,2], halogenated ethers [3][4][5][6][7], methylacetate [8], halogenated aldehydes [9], fluorinated alcohols [10] and halogenated alkanes [11]. For most of these systems, such as the H 2 O. .…”
Section: Introductionmentioning
confidence: 99%
“…As such the overall rate constant for the reaction of OH with CF 3 OCH 2 CH 3 was reported to be 0.5 x 10 -13 which is about three times lower than the experimentally determined value of 1.55 ± 0.25 x 10 -13 cm 3 molecule -1 sec -1 at 298K and 1 atmospheric pressure based on relative rate method using gas chromatography mass spectrometry (GC-MS) detection technique. 13 In order to assess the contribution of each channel to the overall degradation rate, the present study has been undertaken, In this study the individual contribution of different reaction pathways, to the overall rate coefficient for the degradation of the title molecule has been calculated and the branching ratio determined. The aim of this work is to have deep insight into the reaction of CF 3 OCH 2 CH 3 with OH radical using state-of-art computational procedure to get reliable data.…”
Section: Introductionmentioning
confidence: 99%
“…4 Langbein et al reported that the atmospheric effects of all the halogenated anesthetics combined produce a relative contribution to global warming of .03%.…”
Section: Nitrous Oxide: a Global Toxicological Effect To Considermentioning
confidence: 99%